Nose-to-brain translocation of inhaled ultrafine elongated particles: facts and mysteries - Graham, U. M.; Pinto, J. M.; Weuve, J.; Dozier, A. K.; Rogers, R.; Nag, S.; Schneider, J.; Kaufman, J. D.; Bennett, D. A.; Oberdörster, G. (Frontiers in Toxicology, 2025)
In this study, we report that inhaled nanosized elongated mineral particles (EMPs) reach the human central nervous system (CNS) via two neuronal pathways, cranial nerve I (olfactorius) and cranial nerve V (trigeminus), from deposits on the nasal mucosa. High-resolution analytical imaging of autopsied brain tissues from eleven members of a Religious Orders Study (ROS) cohort (Rush Alzheimer’s Disease Center) indicated that EMPs translocate from their nasal deposits to the brain either by the olfactory pathway (presence in the olfactory bulb (OB), olfactory tract, and amygdala) or by the trigeminal pathway (presence in the cerebellum). Sub-nanometer imaging and immunohistochemical (IHC) labeling were used to detect corpora amylacea (CA), abundant numbers of endogenous ferritin nanoparticles, and myelin damage as indicators of inflammation or oxidative stress. The majority of EMPs in the OB were identified as inorganic crystalline and amorphous SiO2 fibers. Amphibole-like fibers (Mg/Si/Fe) were present (length from 25 up to 200 nm), along with lengthened nanoplastics and metallic or carbonaceous fibers. Extensive and consistent demyelination, phosphorylation, wall thickening, and CA bodies (size ranging from 10 nm to ∼10 μm) are present in all studied brain tissues. EMPs are frequently observed inside and outside of CA bodies that occur in close proximity to neurons with myelin damage. The majority of EMPs show shedding of nanosized fiber fragments and ions from their long fiber surfaces and the formation of carbon-rich coronas (physiochemical alterations: bioprocessing). Similar to spherical nanoparticles, EMPs show a tendency to bioprocess, which involves interacting with microglia, astrocytes, and CA. In conclusion, we note that although the presence of ambient EMPs in the OB, amygdala, and cerebellum of human brains is consistent with neuronal translocation from nasal deposits of inhaled EMPs to the human CNS, it remains important to further investigate the potential contribution of nano-EMPs entering from the blood compartment by crossing the blood–brain barrier (BBB) and other potential routes to the CNS.